ANALYZING THE ROLE OF ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION IN MINIMIZING TURNOVER INTENTION - Hermawati, Adya; Sambung, Roby; Haditomo, Alfabetian Harjuno Condro; Hendarto, Totok; Ramlawati; Iswati (Universitas Brawijaya, Indonesia, 2022)
As an organization, hospitals should always make efforts to improve the performance of their employees because those employees will help the hospitals to attain their vision, mission, and goals. This research aims to analyze the effect of organizational climate on turnover intention in mediating organizational commitment and job satisfaction. The research type is a cross-sectional study with a quantitative approach. Data collection is done in one-time observation through a survey involving questionnaires. Items of the questionnaire are arranged on the Ordinal Likert Scale. The data analysis instrument is Variance Based Structural Equation Modelling (SEM), or Second-Order Partial Least Square Program (Smart PLS Version 2.0). The research subject or analysis unit is all employees at Mother-Child Health Hospital of Rembang. Population (N) of research includes all hospital employees, a total of 218 individuals. The employees are divided into clinical staff involved in health care services and non-clinical staff who are definitely not included in the clinical group. The sampling technique is random sampling which takes only some population members to represent the population. There are 70 individuals selected from the workgroup to act as respondents. Then, several conclusions are obtained from the analysis and results of the hypothesis test. A good organizational climate can strengthen organizational commitment. Regarding this position, it is suggested that Mother-Child Health Hospital of Rembang maintain and improve its organizational climate.